2009
DOI: 10.1111/j.1365-2265.2008.03398.x
|View full text |Cite
|
Sign up to set email alerts
|

Adjustment of L‐T4 substitutive therapy in pregnant women with subclinical, overt or post‐ablative hypothyroidism

Abstract: Serum TSH and FT4 measurements are mandatory in pregnant patients and the optimal timing for increasing L-T4 is the first trimester of pregnancy, though many patients require adjustments also during the second and third trimester. The aetiology of hypothyroidism influences the adjustment of L-T4 therapy and SH patients needed a larger increase than OH and PH. Close monitoring during pregnancy appears to be mandatory in hypothyroid women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
34
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 33 publications
2
34
1
1
Order By: Relevance
“…Based on our meta-analysis of the available studies reporting on L-T 4 adjustment in pregnancy (Table 1), the proportion of women requiring adjustment resulted 56% (95% CI: 52-60%), which is considerably lower than the 84% (95% CI: 70-93%) observed in our series. Noteworthy, the two 95%CIs do not overlap and the reported rates exceeded our 84% in only one of the ten identified studies (19). To note, this latter study refers to the most stringent criteria used for L-T 4 adjustment (serum TSH had to maintain below 2.5 mIU/l for the whole duration of pregnancy).…”
Section: Clinical Study a Busnelli And Others Levothyroxine Adjustmenmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our meta-analysis of the available studies reporting on L-T 4 adjustment in pregnancy (Table 1), the proportion of women requiring adjustment resulted 56% (95% CI: 52-60%), which is considerably lower than the 84% (95% CI: 70-93%) observed in our series. Noteworthy, the two 95%CIs do not overlap and the reported rates exceeded our 84% in only one of the ten identified studies (19). To note, this latter study refers to the most stringent criteria used for L-T 4 adjustment (serum TSH had to maintain below 2.5 mIU/l for the whole duration of pregnancy).…”
Section: Clinical Study a Busnelli And Others Levothyroxine Adjustmenmentioning
confidence: 99%
“…On the other hand, it is noteworthy that the results from previous contributions are highly heterogeneous. The proportion varies from 22% (20) to 87% (19). These relevant differences presumably reflect differences in study design (prospective vs retrospective), characteristics of the studied populations, and clinical criteria used to adjust L- In the present study, the positivity of anti-thyroid autoantibodies and, consistently, the autoimmune origin of hypothyroidism resulted statistically significantly associated with the need for L-T 4 adjustment in early pregnancy, indicating that the contribution of the thyroid gland to the maintenance of euthyroidism is further impaired and becomes insufficient during pregnancy.…”
Section: Clinical Study a Busnelli And Others Levothyroxine Adjustmenmentioning
confidence: 99%
“…Levothyroxine administration reduced rates of miscarriage and premature delivery in thyroid antibody-positive women to values similar to those of controls with euthyroid function (Negro et al 2006). The incidence of obstetric complications is decreased when euthyroidism can be achieved and maintained by levothyroxine treatment in pregnant hypothyroid women (Glinoer 1998;Verga et al 2009). However, an improvement in fertility by levothyroxine administration has not yet been proven (Gartner and Reincke 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been shown that miscarriage in women affected by thyroid autoimmunity mainly occurs during the first trimester (Lejeune et al 1993) and patients with recurrent miscarriage (RM) showed rather high incidences of thyroid antibodies (Bussen and Steck 1995) (Reznikoff-Etievant et al 1999). In accordance with the Endocrine Society Guidelines, hypothyroidism in pregnant women is indicated to be treated with levothyroxine, even if subclinical (Gartner and Reincke 2008;Verga et al 2009). The benefit of levothyroxine replacement in pregnant women has been demonstrated by several studies.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of maternal hypothyroidism on pregnancy can be profound, including an associated increased risk of miscarriage, premature delivery, preeclampsia, low birth weight, C-section, fetal death, and decreased infant IQ (2-7). Although there is still controversy regarding the implications of subclinical hypothyroidism and hyperthyroidism on pregnancy outcome (8)(9)(10), there are clear data confirming that pregnancy does alter thyroid function (11), and women on thyroid hormone replacement prepregnancy do need dose adjustments during pregnancy (2,(12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%